Evaluation of nitrate quantification techniques for in-line analysis in drinking water - Hernández-Alpízar, Laura (2015)
The potential of four analytical methods for the quantification of nitrate is determined to be used in a continuous sampling set up: ion chromatography and the ultraviolet spectrophotometric screening, both in their benchtop version, Cadmium reduction with post-reaction and visible light absorption measurement and the direct ultraviolet spectrophotometric absorption screening but using mini-spectrophotometers and in flow injection of the sample and analysis (FIA) techniques. Accessories, toxicity of the reaction products, response, detection and quantification limits, linearity in the range of interest and sensitivity are considered for the evaluation. The direct measurement of ultraviolet absorption with flow injection was the best of the evaluated techniques. It has a linear response in the 0-10 mg/L range, WHO recommended range for drinking water, low reagents and accessories consuming, LOD 0,002 mg/L, LOQ 0,006 mg/L, and good sensitivity in the investigated range, meeting the required characteristics for in-line monitoring systems.